Cell Fusion: Optically Induced Cell Fusion Using Bispecific Nanoparticles (Small 22/2013). Issue 22 (25th November 2013) - Yeheskely‐Hayon, Daniella; Minai, Limor; Golan, Lior; Dann, Eldad J.; Yelin, Dvir
<x xml:space="preserve">Abstract</x> The image shows a high magnification scanning electron microscopy image of a dendritic (false color blue) and malignant B (false color green) cell pair coupled by bispecific gold nanoparticles. As described on page 3771 by D. Yeheskely‐Hayon and co‐workers, the cell pairs are irradiated by a sequence of femtosecond laser pulses, resulting in a wide‐spread fusion and subsequent formation of dendritic‐B cell hybrids, which could be used for stimulating the immune system to eliminate tumor cells. This novel approach for selective induction of cell fusion using bispecific nanoparticles and laser pulses could be useful for a variety of applications that call for selective fusion between cells within a large heterogenic cell population. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>